Characteristics of Individuals at Risk for Spinocerebellar Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at University Hospital of Bonn and 13 other centers in Germany, France, and Italy conducted a prospective, longitudinal observational study (2008-2011) of offspring or siblings of patients with spinocerebellar ataxias (SCA)-1, 2, 3, and 6.